'Challenging Stereotypes' as a Core Competence in Creative Entrepreneurship: Insights from ArtiShock Theatre, Kazakhstan. (December 2022) - Ryabova, Kristina; Fomina, Victoria; Ghosh, Anjan
Although scholarly interest in creative entrepreneurship (also known as cultural industry) is gaining traction, the development of organizational competences beyond the creative offerings have remained underexplored. Such omission is surprising as an organization in creative industry cannot be solely dependent on creative offerings. It needs to focus on other aspects of business. To explore the possible link between product creativity and business model, we conduct a study on ArtiShock Theatre—Kazakhstan's first independent theatre. Our study suggests that a creative enterprise can address both competition and environmental shocks through the process consisting of exploratory re-forming, experimental organizing leading to the development of 'challenging stereotypes' as a core competence. Our study shows that such core competence might be evolved into a dynamic capability to handle environmental changes.